2012
DOI: 10.1111/ddi.12008
|View full text |Cite
|
Sign up to set email alerts
|

Where do they come from and where do they go?European natural habitats as donors of invasive alien plants globally

Abstract: Aim The percentage of alien species found in a given habitat depends on the habitat vulnerability to invasion (invasibility) and the number of species introduced (propagule pressure). However, the global pool of alien species suited to a given habitat also varies. Here, we identify donor habitats of invasive alien plant species originating from Europe, examine the match between habitats they occupy in Europe and recipient areas and test whether donor habitats of invasive plants tend to be vulnerable or resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 32 publications
3
70
0
Order By: Relevance
“…Another major European alien species inventory compiled over the last decades is the North European and Baltic Network on Invasive Alien Species (NOBANIS; www.nobanis.org), a joint effort of 18 European countries (Hulme & Weser 2011). For other continents, a comprehensive database, primarily focused on native taxa but also including the distribution of a complete alien flora, is the regularly updated BONAP database (Kartesz & Meacham 1999, which has been used in a number of intercontinental analyses of plant invasions , Kalusová et al 2013, van Kleunen et al 2015. However, BONAP has not yet been used for a thorough taxonomic description of the patterns in the alien flora of North America.…”
Section: Introductionmentioning
confidence: 99%
“…Another major European alien species inventory compiled over the last decades is the North European and Baltic Network on Invasive Alien Species (NOBANIS; www.nobanis.org), a joint effort of 18 European countries (Hulme & Weser 2011). For other continents, a comprehensive database, primarily focused on native taxa but also including the distribution of a complete alien flora, is the regularly updated BONAP database (Kartesz & Meacham 1999, which has been used in a number of intercontinental analyses of plant invasions , Kalusová et al 2013, van Kleunen et al 2015. However, BONAP has not yet been used for a thorough taxonomic description of the patterns in the alien flora of North America.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 29 articles addressed a wide range of particular species: ten articles focused on aquatic species (e.g., Ateweberhan et al 2011;Guizien et al 2014;Landguth et al 2014), nine on plant species (e.g., Arianoutsou et al 2013;Gonzalez-Moreno et al 2013;Kalusova et al 2013), five on bird or bat species (e.g., Erickson et al 2015;Furness et al 2012;Tranquilla et al 2013) and five on other animal species (e.g., Drever et al 2012;Dufresnes and Perrin 2015;Lacasella et al 2015). Furthermore, 15 addressed whole habitats (e.g., Gauthier et al 2013;Giakoumi et al 2015;Kalusova et al 2013), and four focused on the vulnerability of the protected area itself (e.g., Aretano et al 2015;Cruz-Elizalde et al 2015;Tomczyk 2011). Eight of the 54 articles related to conservation ecology investigated the vulnerability to invasive species (e.g., Hulme 2012; Kalusova et al 2013;Olden et al 2011).…”
Section: Vulnerability Of Different Ecosystems and In Different Discimentioning
confidence: 99%
“…Previous studies have shown that potential pathways of IPS may only become apparent in the late stages of invasion (Meier et al, 2014;Donaldson et al, 2014), and our findings indicate that the potential pathways of IPS in PAs play an important role in the intentional introduction of IPS worldwide. Thus, IPS may not only impact biodiversity and habitat quality within PAs Hulme et al, 2014), but also have the potential to easily spread to adjacent PAs (Thuiller et al, 2005;Kalusová et al, 2013). Hence, PAs may promote the development of potential pathways for IPS and then increase the risk of invasion on a global basis, given that PA management is not being enhanced.…”
Section: Preventing and Controlling Ips In Protected Areasmentioning
confidence: 99%
“…Invasive plant species (IPS) have the potential to threaten global biodiversity in the face of global climatic changes (Kalusová et al, 2013). However, the relationship between IPS and climate change is complex (Hellmann et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation